2012
DOI: 10.1159/000338178
|View full text |Cite
|
Sign up to set email alerts
|

Renalase, a Novel Enzyme Involved in Blood Pressure Regulation, Is Related to Kidney Function but Not to Blood Pressure in Hemodialysis Patients

Abstract: Renalase, secreted by the kidney, degrades catecholamines and may play a role in the regulation of sympathetic tone and blood pressure. The aim of this study was to assess serum renalase levels in hemodialysis patients and their relationship to blood pressure control, type of antihypertensive therapy and the presence of residual renal function. Results: The mean serum renalase in the study cohort was significantly higher than in the control group (27.53 ± 7.18 vs. 3.86 ± 0.73 µg/ml, p < 0.001). The serum renal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 34 publications
4
42
2
1
Order By: Relevance
“…One of these studies showed that the serum renalase level was 4 times higher in 34 CKD patients (stage 5) than in 20 healthy controls [22]. Similarly, Zbroch et al (2012) in their study showed that the serum renalase level was higher in 104 CKD patients (stage 5) than in healthy volunteers [21]. The present study likewise showed a strong negative correlation between serum renalase and eGFR (r=−0.51, p<0.001) and strong positive correlation with renal function as assessed by cystatin-C (r=0.37, p<0.05) as shown in Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these studies showed that the serum renalase level was 4 times higher in 34 CKD patients (stage 5) than in 20 healthy controls [22]. Similarly, Zbroch et al (2012) in their study showed that the serum renalase level was higher in 104 CKD patients (stage 5) than in healthy volunteers [21]. The present study likewise showed a strong negative correlation between serum renalase and eGFR (r=−0.51, p<0.001) and strong positive correlation with renal function as assessed by cystatin-C (r=0.37, p<0.05) as shown in Figs.…”
Section: Resultsmentioning
confidence: 99%
“…According to two previous studies, the three main key factors that are responsible for the regulation of renalase blood level are the renal perfusion, renal function, and catecholamine level. There was also a direct relationship between renalase, glomerular filtration rate, and kidney mass, resulting in marked renalase deficiency in CKD patients (stage 5) [12,20]. On the other hand, there are many recent studies that reported a negative relationship between renalase level and renal function, with the result that renalase level is markedly increased in CKD patients (stage 5) [21,22].…”
Section: Resultsmentioning
confidence: 99%
“…The same authors also investigated in chronic kidney disease patients the impact of hemodialysis and peritoneal dialysis 16 on blood serum renalase They concluded that impairment of renal function correlates with increased renalase levels [26][27][28], which was found up to 10-fold higher in anuric patients that underwent bilater nephrectomy in comparison to healthy subjects [26]. Finally, it was reported that stroke and hypertensions were associated to lower serum renalase concentrations in a hemodialysis population [27].…”
Section: Nadph-dependent Diaphorase Reactions With Various Artificialmentioning
confidence: 97%
“…A renalase concentration of 0.1 mg per gram wet tissue has been estimated in the kidneys by immunoblotting [10]. Data on the absolute concentration of renalase in human blood plasma have been explicitly reported only recently, as determined by ELISA, showing that it is about 4 g/ml in healthy individuals, corresponding to 0.1 M [23][24][25][26][27][28]. Murine renalase gene expression was observed by reverse transcriptase PCR in kidney, testicle, liver, heart, 12.5-days whole embryo, brain, and skeletal muscle [16].…”
Section: Renalase Isoforms and Gene Expression Patternmentioning
confidence: 99%
“…На сегодняшний день несколько исследовательских групп подтвердили присутствие реналазы в плазме [1,[11][12][13]. При этом исследование корреляции между уровнем реналазы, значениями артериального давления и функцией почек, проведённое на 130 пациентах после операции трансплантации сердца, выявило зависимость между уровнем сывороточной реналазы и функцией почек, но не артериального давления [12,13].…”
unclassified